Cloning, nucleotide sequence, and characterization of genes encoding the secretion function of the Pasteurella haemolytica leukotoxin determinant. - Strathdee, C A (1989)
The structural gene of the Pasteurella haemolytica leukotoxin determinant is highly homologous to that of the Escherichia coli hemolysin determinant, which also encodes a specialized set of genes involved in the secretion of the hemolysin. In this report, we describe the cloning and nucleotide sequence of the analogous secretion genes from P. haemolytica which make up the remainder of the leukotoxin determinant. The secretion genes were cloned directly from the P. haemolytica chromosome to form the recombinant plasmid pPH5B. By subcloning the secretion genes together with the leukotoxin structural gene, the cloned leukotoxin determinant was reconstructed on a single plasmid, pLKT52, which directs the synthesis of active leukotoxin to the culture supernatant when expressed in E. coli. DNA sequence analysis showed the presence of two secretion genes, designated lktB and lktD in order of their genetic organization, which code for proteins of 79.7 and 54.7 kilodaltons, both of which were detected when pLKT52 was expressed in E. coli minicells. The lktB and lktD genes were found to be highly homologous to the hlyB and hlyD secretion genes of the hemolysin determinant, and the predicted LktB-HlyB and LktD-HlyD proteins were 90.5 and 75.6% homologous. Nucleotide sequence homology between the leukotoxin and hemolysin determinants was limited to the C, A, B, and D coding regions, although the presence of similar transcriptional terminators in the A-B intercistronic region is suggestive of a similar transcriptional organization. On the basis of these data, we hypothesize that the two determinants share a common evolutionary history and are prototypes for a widely disseminated family of virulence factors, the RTX cytotoxins.